Extension Educators and Volunteer Leaders: Evaluation of Fitness Outcomes Among Participants in Community Strength Training Classes - Washburn, Lisa Tucker; Traywick, LaVona; Garrison, M. E. Betsy (Frontiers in Public Health, 2020)
Volunteer-led strength training classes can expand access, improve exercise adherence, and enhance intervention sustainability for older adults. This study compared participant functional fitness outcomes between volunteer-led and Extension educator-led StrongWomen strength training groups in community settings. Change scores for participants (n = 317) were calculated for six Senior Fitness Test (SFT) measures. A non-parametric analysis of independent samples to determine SFT score differences between participant groups (educator-led and volunteer-led) showed no significant differences. Volunteers and professionals, like Extension educators, may be similarly effective in conducting community-based strength training classes resulting in improved functional fitness outcomes. We offer recommendations for organizations seeking to adopt similar approaches.